THE IMPERATIVE SENTENCE IN DOLOKSANGGUL TOBA BATAK LANGUAGE - Imelda Malawaty Simorangkir; Yosi M. Passandaran (Pujangga: Jurnal Bahasa dan Sastra, 2016)
ABSTRACTThe purpose of the research “The Imperative Sentence in Doloksanggul Toba Batak Language” is to find out thekinds of the imperative sentence structure and the characteristics of the imperative sentence between Toba Bataklanguage in general and Toba Batak Doloksanggul. The theory is about kinds of sentence, especially imperativesentence. The imperative sentence also be called as a command sentence. Besides as a command sentence,imperative sentence also used to say request, prohibition that can be formed in a sentence. These sentences can befound in every language such as in Indonesian, the language of the tribes as well as foreign languages. Everylanguage has characteristics itself, such as in Doloksanggul Toba Batak language in North Sumatera, Indonesia.Batak language Doloksanggul has differences with the Batak language is generally. The characteristics ofimperative sentences in Doloksanggul Toba Batak language has differences. The differences can be found in thestructure, the using of particle, and the using of vocabularies. The descrptive analysis method was used in thisresearch. The analysis is taken from the interview for collecting the information. The result is the differences ofimperative sentence characteristics between Toba Batak language in general and Doloksanggul Batak Toba are Keywords: types of imperative sentence, characteristics of imperative sentence,Doloksanggul Toba Batak language.